Sokoto Caliphate Literatures: Importance on Relieving or Remediating Drug Abuse in Northern Nigeria and Muslim Societies - Tambari Abbas Bashar (International Journal of Applied and Scientific Research, 2024)
Drug abuse is a menace ravaging in the modern societies. The dangers of drug abuse are plain and ubiquitous and all-pervasive. It causes effects on the body of abusers and non-users. Effects include deterioration of (physical and mental) health, school drop out, school absenteeism, crime, frauds, violence, joblessness, addiction, withdrawal effects, death, injuries, broken homes or families, and many other consequences. That is why it is pertinent to apply the lessons of Sokoto Caliphate literature in preventing drug absolutely abuse in society. The Northern Nigeria Muslims, others Muslims, and even other societies can learn greatly in Sokoto Caliphate literature to tap lessons for preventing drug abuse. The Sokoto Caliphate literature is simple, practical, relevant, and is vast. Literatures in Sokoto Caliphate are due to the jihad orchestrated by Shehu Usmanu Danfodiyo and his friends in the 19th century Hausa states. Books such as Ihya'ussunah, Nurul Albab, WasiyyatuSshaikh, Ulumul Muamalah, Udadu dai, Lubabul madkhal are vital in drug abuse prevention for preferring solutions to the menace. The solutions include methods to purify soul and mind from filthy things such as anxiety, fear, depression, sadness, frustrations. The main thing to cure these is true Iman with Allah and stepping on the status of Ihsan. In the literatures, punishment for offenders for taking drugs is outline, need for parental care, sanitizing environments (by governments) are disclosed. The other methods were fully discoursed. It is important to apply the lessons from the Sokoto Caliphate literatures to solve the prevailing drug abuse menace in the environments (societies)